Characterisation Of Pectate Lyase Pelq1 From Saccharobesus Litoralis - Melissa Lian, Qianyue (2024)
The pelQ1 gene from the marine bacterium Saccharobesus litoralis CCB-QB4 encodes a pectate lyase that consists of two domains, which are polysaccharide lyase family 1 (PL1) and carbohydrate-binding module family 13 (CBM13). CBM13 which is involved in substrate binding is often found in pectate lyases (Pels) from marine sources but not terrestrial sources. Moreover, the study of marine Pels is lacking since pectin is not one of the major sources of carbohydrates in the marine environment. Therefore, this study aimed to elucidate the cleaving mechanism of PelQ1 by comparing the activity of the full-length enzyme (PelQ1-Full) and the truncated enzyme with CBM13 removed (PelQ1-PL1). Both enzymes were cloned, purified, characterized, and their cleaving mechanisms were elucidated. PelQ1-Full exolytically cleaved the substrate polygalacturonic acid (PGA) to produce a majority of unsaturated trigalacturonic acid; however, it cleaved the citrus pectin (CP) into a majority of unsaturated digalacturonic acid when high enzyme concentrations were used. PelQ1-Full worked in an optimal condition of pH 9.0, 30°C, and 0.6 mM CaCl2. Comparison between the two enzymes showed that there was a slightly higher catalytic efficiency (kcat/KM) towards PGA than CP, while TLC results showed that the CBM13 domain might help substrate binding. The AlphaFold homology model of the PL1 domain showed that it had a structure of parallel β-helix and a high sequence similarity with PelC of Dickeya dadantii. The CBM13 domain showed a structure of β-trefoil fold similar to other CBM13 domains.